Implementation of EMIS 4.0 Application Management in Madrasah Education Data Collection to Support the Policy of the Ministry of Religion of the Republic of Indonesia at Tsanawiyah Madrasah Ma`Had Al-Zaytun, Gantar District, Indramayu - Alisah, Siti; Siswoyo, Mukarto; Permana, Ipik; Prayitno, Arief (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
Implementation of the Education Management Information System 4.0 at Madrasah Tsanawiyah Ma`had Al-Zaytun, Gantar District, Indramayu Regency, there are problems faced, namely the implementation of duties and responsibilities as an EMIS 4.0 operator, collection of student files (diplomas, family cards and certificates), internet network in work investigations, and difficulties in accessing the EMIS 4.0 application due to server errors. This research aims to determine the implementation of the EMIS 4.0 application policy in Madrasah Tsanawiyah Ma`had Al-Zaytun, supporting and inhibiting factors for implementing EMIS 4.0 in Madrasah Tsanawiyah Ma`had Al-Zaytun, and what efforts and strategies will be carried out by Madrasah Tsanawiyah Ma`had Al-Zaytun in implementing EMIS 4.0. The research method uses a qualitative approach with a descriptive-qualitative type. By collecting data through observation, interviews and documentation. The data source was taken using a purposive sampling technique to select 10 informants. The data analysis techniques used are data condensation, data presentation, and drawing conclusions. The results of this research indicate that the implementation of the Education Management Information System 4.0 at Madrasah Tsanawiyah Ma`had Al-Zaytun, Gantar District, Indramayu Regency is quite good. The strategies that will be carried out by Madrasah Tsanawiyah Ma`had Al-Zaytun in implementing EMIS 4.0. In July, namely graduating 9th grade students, raising 7th and 8th grade students, creating groups and inspiring students in groups and creating a new 7th grade EMIS database, July-August which is carried out with Computer-Based National Assessment Data Collection (ANBK) or Minimum Competency Assessment (AKM), August-September namely detailed 7th grade EMIS data entry, October the activity is updating the 9th grade EMIS data based on statement letters and files for Madrasah Examinations as well as PD verification and Madrasah Examination Data Base (PDUM), October-December Finalization of EMIS data, January-March completes data for class 8 and especially class 7, March-April focuses on EMIS class 9 and May-June final checks for class 7 and 8.